Evaluation of Nonlinear Wave Separation Method to Assess Reflection Transit Time: A Virtual Patient Study - Manoj, Rahul; Raj Kiran, V; Nabeel, P M; Sivaprakasam, Mohanasankar; Joseph, Jayaraj (2021 43rd Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC), 2021)
Conventional methods to calculate reflection transit time (RTT) is based on pulse counter analysis. An alternative to this approach is separating forward and backward components from a pulse waveform to calculate the RTT. State-of-the-art in wave separation requires simultaneously measured pressure and flow velocity waveforms. Practically, getting a simultaneous measurement from a single arterial site has its limitations, and this has made the translation of wave separation methods to clinical practice difficult. We propose a new method of wave separation analysis that requires only a single pulse waveform measurement using a multi-Gaussian decomposition approach. The novelty of the method is that it does not require any measured or modelled flow velocity waveform. In this method, the pulse waveform is decomposed into the sum of Gaussians and reconstructed based on model criteria. RTT is calculated as the time difference between normalized forward and backward waveform. The method's feasibility in using RTT as a potential surrogate is demonstrated on 105 diverse selections of virtual subjects. The results were statistically significant and had a strong correlation (r>79, p<0.0001) against clinically approved artery stiffness markers such as Peterson's elastic modulus (Ep), pulse wave velocity (PWV), specific stiffness index (β), and arterial compliance (AC). Out of all the elasticity markers, a better correlation was found against AC.Clinical Relevance-This simulation study supplements the evidence for the dependence of pulse wave reflections on arterial stiffness. It provides a new method to study wave reflections using only a single pulse waveform.